Crop improvement, adoption and impact of improved bean varieties in Sub Saharan Africa - Muthoni Andriatsitohaina, Rachel; Andrade, Robert Santiago (2015)
The crop improvement research effort of the Consultative Group on International Agricultural Research (CGIAR) centers and their national agricultural research systems (NARS) partners has had a large impact on world food production. Although bean impact has been documented in a number of past studies, the last comprehensive study of the international crop improvement effort, organized by the Standing Panel for Impact Assessment (SPIA, formerly the Impact Assessment and Evaluation Group), was based on data collected a decade ago (Evenson and Gollin, 2003 based on 1997-98 data). Important changes have occurred in the funding and conduct of the international crop improvement effort and in the general climate for agriculture in the developing world since the completion of the Evenson and Gollin study.The level and focus of funding for research in the NARS and in the CGIAR centers have fluctuated greatly, and the role of the private sector has evolved. Yet, the importance of the CGIAR/NARS crop improvement effort in feeding the world is arguably as important today as it has been at any time in history. The steady uptake and turnover of crop varieties is fundamental to realizing a Green Revolution in Africa, and it is still important for helping achieve income growth for numerous poor rural households. But our present understanding of improved variety adoption by crop, by location, by adopter and by source is limited in Africa. The data seeks to redress this anomaly, by providing a versatile database on bean variety adoption by crop, by location, by adopter and by source in sub-saharan countries. The following countries are covered: Burundi, DRCongo, Ethiopia, Malawi, Mozambique, Rwanda, Tanzania, Uganda and Zambia.